2021
DOI: 10.1016/j.mcpro.2021.100095
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Triglyceride Lipase Loss Promotes a Metabolic Switch in A549 Non–Small Cell Lung Cancer Cell Spheroids

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“… 66 68 A very recent study has reported that loss of ATGL function causes a pro-Warburg effect in lung cancer cell spheroids but not in two-dimensional (2D) cell cultures. 69 These studies indicate a tumor-suppressive function of ATGL. Conversely, other studies have suggested that elevated ATGL levels promote tumorigenesis of non-small-cell lung carcinomas and colon cancer cells.…”
Section: Discussionmentioning
confidence: 85%
“… 66 68 A very recent study has reported that loss of ATGL function causes a pro-Warburg effect in lung cancer cell spheroids but not in two-dimensional (2D) cell cultures. 69 These studies indicate a tumor-suppressive function of ATGL. Conversely, other studies have suggested that elevated ATGL levels promote tumorigenesis of non-small-cell lung carcinomas and colon cancer cells.…”
Section: Discussionmentioning
confidence: 85%
“…Compared to 2D cultured cells, the metabolic profile of 3D cultured ATGL-KO A549 cells and their microenvironment more closely resembled the actual situation in vivo (9).…”
Section: Lung Cancermentioning
confidence: 91%
“…The reason for this inconsistent result at the cellular and animal level may be the difference in the microenvironment in which the tumor cells are located. Compared to 2D cultured cells, the metabolic profile of 3D cultured ATGL-KO A549 cells and their microenvironment more closely resembled the actual situation in vivo ( 9 ).…”
Section: Different Roles Of Atgl In Tumorsmentioning
confidence: 96%
See 2 more Smart Citations